STRATEGI KEBIJAKAN PEMERINTAH KABUPATEN ROKAN HILIR DALAM PENCEGAHAN KEBAKARAN LAHAN DAN HUTAN (KARLAHUT) TAHUN 2015 - Amin, Muhammad Rizwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is based on issues of land and forest fires occurring every year in Rokan Hilir Regency. This study also reviewed in 2015 because it was based on Bupati Regulation made in 2011, after 4 Year Regulation of Regent running, the authors see various causes of development and problems that occur related to prevention of land and forest fires in Rokan Hilir Regency in 2015 with the prevention which has been done but the fire point is still widely found.The types and methods used are qualitative research. Location and time of research conducted in Rokan Hilir Regency in 2015. Technique of collecting data of this research that is by doing interview and documentation equipped with supporting data obtained from mass media. Interviews were conducted with BPBD, SATLAKDALKARLAHUT, BLH, and other relevant agencies participating in the prevention of land and forest fires in Rokan Hilir District in 2015.The results of this study explain that the government of Rokan Hilir Regency and related fires and forest fires less than the maximum in prevention is evidenced by the number of hotspots through TERRA satellite reaching 733 hotspots. Since the regent regulation that has been made to form SATLAKDALKARLAHUT in 2011 and has 4 years running until 2015. According to data BPBD also still many obstacles that can not be overcome by the government and SATLAKDALKARLAHUT in 2015.Keywords: Policy, Government, Land and Forest Fire